Long term outcomes of pituitary adenomas in Multiple Endocrine Neoplasia type 1: a nationwide study - Valdés, Nuria; Romero, Ana; Diego, Estrella; Calatayud, María; Lamas, Cristina; Araujo-Castro, Marta; Álvarez-Escolá, Cristina; Díaz, José A.; Alcázar, Victoria; Sastre, Julia; Martínez, Rosa; Oriola, Josep; et al. (Frontiers in Endocrinology, 2024)
Introduction: Historically, Multiple Endocrine Neoplasia type 1 (MEN1)-related pituitary adenomas (PAs) were considered more aggressive and treatment-resistant than sporadic PAs. However, recent studies suggest similarities in their behavior. This study aimed to evaluate the long-term outcomes of MEN1 PAs and identify predictive factors. Methods: Nationwide multicenter retrospective cohort study of MEN1-related PAs with a minimum 1-year follow-up, collecting patient demographics, germline MEN1 pathogenic variants (PV), PA size, secretory profile, radiological characteristics, treatments, and outcomes. Results: We analyzed 84 PAs, 69%in females and 31% in males (P<0.001), diagnosed at a mean age of 35.2±14.9 years, mostly through screening (60.7%). Median follow-up was 9 years (IQR:4-16). Prolactin-secreting PAs (PRLomas) (53.5%) and microadenomas (65.5%) were most common. Dopamine agonist treatment was first line for 16 macroPRLomas and 25 microPRLomas, 60.9% of them achieved PRL normalization. There was no significant association observed with tumor size, sex, treatment duration or MEN1 PV. The risk of progression from micro-PA to invasive macro-PA was 7.2% (4/55), after a follow-up of 8 years (IQR:4-13), all of them were microPRLomas. Kaplan-Meier estimation curve showed significantly higher progression probability in microPRLomas than in other microadenomas subtypes (P=0.017) or microNFPAs (P=0.032). No differences were found between sex, age, or germline MEN1 PV. Conclusions: MEN1-related micro-PAs have a low risk of progressing to invasive macro-PAs, regardless of sex, age at diagnosis, or MEN1 germline PV. The risk is higher for microPRLomas over the long term. Therefore, long-term surveillance with reduced frequency, rather than intensive short-term monitoring, may be appropriate for patients with MEN1-related PAs.